Providing Assistance for Older Adult Financial Exploitation Victims: Implications for Clinical Gerontologists. Issue 4 (8th August 2019) - Lichtenberg, Peter A; Hall, Latoya; Gross, Evan; Campbell, Rebecca
ABSTRACT: Background and Objective : Despite the growth of financial exploitation research in the past decade, almost none has focused on older urban adults, and especially urban African Americans. The Success After Financial Exploitation (SAFE) program provides individual financial coaching to older urban adults. Methods : We use community education, delivered separately to older adults and to the professionals who serve them, to raise awareness about financial exploitation (FE) and to motivate referrals for financial coaching. This paper describes the program and methodology, and uses case examples and preliminary research to investigate the intersection of FE and physical and mental health functioning. Results : SAFE participants were able to repair their credit scores, reduce new financial burdens, and even recover monies they had lost due to FE. Case examples illustrate how financial scams and identity theft impacts urban older adults. Participants were assessed prior to the provision of services, and SAFE participants performed poorer on executive functioning tasks than participants in the control group. They also reported more physical health problems and anxiety and depressive symptoms. SAFE participants also had significantly higher risk scores on a financial decision-making scale. Conclusion : Study findings advance our understanding of the impacts of FE on cognitive functioning, mental health, and financial decision-making. Clinical Implications : Clinicians need to be more attuned to the financial health of their older clients, who, if they are struggling with financial exploitation, may also be suffering from problems with cognitive functioning and physical and mental health.